2007
DOI: 10.1038/nm1637
|View full text |Cite
|
Sign up to set email alerts
|

Protein carbamylation links inflammation, smoking, uremia and atherogenesis

Abstract: Post-translational modification and functional impairment of proteins through carbamylation is thought to promote vascular dysfunction during end-stage renal disease. Cyanate, a reactive species in equilibrium with urea, carbamylates protein lysine residues to form epsilon-carbamyllysine (homocitrulline), altering protein structure and function. We now report the discovery of an alternative and quantitatively dominant mechanism for cyanate formation and protein carbamylation at sites of inflammation and athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
739
3
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(770 citation statements)
references
References 47 publications
12
739
3
16
Order By: Relevance
“…138 In humans, isocyanic acid is a product of the spontaneous decomposition of urea, but at sites of inflammation and atherosclerotic plaques it may also derive from the oxidation of thiocyanate by MPO. 138,139 Double immunofluorescence assays revealed colocalization of MPO with carbamylated proteins within atherosclerotic plaques. 139 Intriguingly, HDL isolated from human atherosclerotic lesions carried high amounts of carbamyllysines.…”
Section: Protein Carbamylationmentioning
confidence: 99%
See 2 more Smart Citations
“…138 In humans, isocyanic acid is a product of the spontaneous decomposition of urea, but at sites of inflammation and atherosclerotic plaques it may also derive from the oxidation of thiocyanate by MPO. 138,139 Double immunofluorescence assays revealed colocalization of MPO with carbamylated proteins within atherosclerotic plaques. 139 Intriguingly, HDL isolated from human atherosclerotic lesions carried high amounts of carbamyllysines.…”
Section: Protein Carbamylationmentioning
confidence: 99%
“…138,139 Double immunofluorescence assays revealed colocalization of MPO with carbamylated proteins within atherosclerotic plaques. 139 Intriguingly, HDL isolated from human atherosclerotic lesions carried high amounts of carbamyllysines. 140,141 These results are consistent with the assumption that HDL trapped in the vascular wall becomes a target for carbamylation.…”
Section: Protein Carbamylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, human studies in patients with CKD have suggested that MPO plays an important role. For example, MPO-derived protein carbamylation is associated with CVD in the CKD population (46)(47)(48)(49). Plasma MPO levels increase with each stage of CKD and are linked to CVD mortality in patients with end-stage renal disease (ESRD) who are undergoing peritoneal dialysis (50)(51)(52)(53).…”
mentioning
confidence: 99%
“…19 Protein modification by carbamylation of ε-NH 2 group of lysine has been particularly reported. 17,20,21 R-Amino groups of alanine, cysteine, and glycine have also been reported as possible carbamylation sites. [22][23][24] To the best of our knowledge, the present communication represents the first experimental report on carbamylation of N-terminal proline in protein.…”
mentioning
confidence: 99%